2013
DOI: 10.3390/ijerph10030950
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Site Study on Knowledge, Attitudes, Beliefs and Practice of Child-Dog Interactions in Rural China

Abstract: This study examines demographic, cognitive and behavioral factors that predict pediatric dog-bite injury risk in rural China. A total of 1,537 children (grades 4–6) in rural regions of Anhui, Hebei and Zhejiang Provinces, China completed self-report questionnaires assessing beliefs about and behaviors with dogs. The results showed that almost 30% of children reported a history of dog bites. Children answered 56% of dog-safety knowledge items correctly. Regressions revealed both demographic and cognitive/behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Consistent with the broader literatures on pediatric drowning in rural China [5,16,17] and other pediatric unintentional injuries [18,19], we found that boys demonstrated more risky self-reported and simulated behaviors and had higher rates of non-fatal drowning experiences than girls even though they shared similar cognitive levels of safety knowledge and perceived vulnerability. The results may reflect boys' higher levels of sensation seeking and hence risk-taking tendencies in the face of desirable but risky situations [20].…”
Section: Risk Factors Of Pediatric Drowning In Rural Chinasupporting
confidence: 89%
“…Consistent with the broader literatures on pediatric drowning in rural China [5,16,17] and other pediatric unintentional injuries [18,19], we found that boys demonstrated more risky self-reported and simulated behaviors and had higher rates of non-fatal drowning experiences than girls even though they shared similar cognitive levels of safety knowledge and perceived vulnerability. The results may reflect boys' higher levels of sensation seeking and hence risk-taking tendencies in the face of desirable but risky situations [20].…”
Section: Risk Factors Of Pediatric Drowning In Rural Chinasupporting
confidence: 89%
“…We developed this questionnaire for use in pilot research with similar age groups of children in rural China and it demonstrated adequate external validity (significant correlation with risk perception, r = −.43, p < .01; and risky interactions with dogs, r = −.23, p < .01) (Shen et al, 2013a). In the present study, the measure had inadequate psychometric properties, so WLSMV-based factor analysis was conducted and revealed 6 items that did not load well onto the primary construct of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Most of study reported that children are mostly affected with percent varying from 26 to 66 percent but none tried to estimate the risk involved in children as compared to general population. 4,[9][10][11][12][13] We couldn't find any study with incidence in the children less than 15 years and various social classes. The study found that age and socio-economic status are important determinants of dog bite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,9,10,13 The ownership of pet dog (9.7%) is relatively low in present study area as compared to other studies. 12,14 Bust most importantly care of pet dog is grossly unsatisfactory whether it veterinary consultation (24%), use of dog collar (3%) or dog vaccination (34%). This is in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%